2014
DOI: 10.1111/trf.12536
|View full text |Cite
|
Sign up to set email alerts
|

The success of our patient blood management program depended on an institution‐wide change in transfusion practices

Abstract: Our success was achieved through hospital-wide physician buy-in toward a restrictive transfusion approach. We hope to encourage others to consider PBM for improved patient outcomes and blood conservation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
62
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(65 citation statements)
references
References 18 publications
1
62
0
2
Order By: Relevance
“…The proportion of 2-unit RBC transfusions decreased from 47% before to 15% after this intervention [96]. A second center similarly reported a reduction in 2-unit RBC orders (48% to 33%) and an increase in 1-unit RBC transfusions (22-48%), before and after, respectively, implementing a comprehensive education and audit program promoting restrictive transfusion practices [97]. A recent literature review found that while CDS can improve RBC usage, further data are needed to assess whether CDS can improve plasma and platelet use utilization [98].…”
Section: Improving Blood Utilization: the Stanford Experiencementioning
confidence: 79%
“…The proportion of 2-unit RBC transfusions decreased from 47% before to 15% after this intervention [96]. A second center similarly reported a reduction in 2-unit RBC orders (48% to 33%) and an increase in 1-unit RBC transfusions (22-48%), before and after, respectively, implementing a comprehensive education and audit program promoting restrictive transfusion practices [97]. A recent literature review found that while CDS can improve RBC usage, further data are needed to assess whether CDS can improve plasma and platelet use utilization [98].…”
Section: Improving Blood Utilization: the Stanford Experiencementioning
confidence: 79%
“…After full texts were examined, 24 records were judged to be eligible. Fourteen records excluded after examining full texts are shown in Supplementary Table S2 [32][33][34][35][36][37][38][39][40][41][42][43][44][45].…”
Section: Search Resultsmentioning
confidence: 99%
“…To optimize utilization of blood products and to identify the ordering physician in case of any audit, it is beneficial to adopt a physician order entry with a clinical decision support based on electronic medical records [14,17]. For the purposes of obtaining informed consent from a patient for the transfusion of allogeneic blood products before transfusion (or after it, when urgently needed), handwritten or computer-generated forms (ideally a separate sheet of paper) should be used that comprehensively includes a detailed outline of transfusion benefits, risks, and alternatives.…”
Section: Patient-centered Decision Makingmentioning
confidence: 99%
“…There is a large amount of research evidence that the successful implementation of PBM reduces perioperative blood loss and transfusion needs [13][14][15][16][17][18][19][20], perioperative morbidity [13,16], mortality [14,16], length of hospital stay [14,16], and costs [21]. In this respect, the World Health Organization has officially been urging member states to implement PBM since 2010 (WHA63.12).…”
mentioning
confidence: 99%
See 1 more Smart Citation